A retrospective study about incidental appendectomy during the laparoscopic treatment of intussusception - Liu, Tao; Wu, Yibo; Xu, Weijue; Liu, Jiangbin; Sheng, Qingfeng; Lv, Zhibao (Frontiers in Pediatrics, 2022)
Purpose: We aim to see incidental appendectomy (IA) was worth or not during the laparoscopic treatment of intussusception. Methods: This study included forty-eight patients who underwent a laparoscopic procedure for idiopathic intussusception without intestinal resection between April 2014 and April 2021. The Chi-square or Fisher's exact tests for categorical variables and the Student t-test for continuous variables were used to analyze and compare patient characteristics. Results: IA was performed on 63% (30/48) of patients after surgical reduction, while 18 (37%), did not. Patients who underwent IA had a higher total cost (16618+2174 vs.14301+5206, P=0.036), and a longer mean operation duration (59+19 vs.45+21, P=0.025). The distribution of the PO time, length of hospital stay, PCs, and RI did not differ significantly. The histopathological evaluation of the 30 resected appendices revealed five (17%) with signs of acute inflammation, 20 (66%) with chronic signs of inflammation, and five (17%) with inconspicuous appendices. Conclusions: IA is linked to a longer average operation time and a higher total cost. There is insufficient evidence to recommend IA during laparoscopic intussusception treatment. The risks and benefits of IA need further study.